2020
DOI: 10.3168/jds.2019-17920
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of phosphatase and tensin homolog (PTEN) inhibits fatty acid oxidation and reduces very low density lipoprotein assembly and secretion in calf hepatocytes

Abstract: BSA); cells infected with Ad-shPTEN for 48 h and then treated with 1.2 mM FFA and 2% BSA for another 24 h (Ad-shPTEN + 1.2 mM FFA). Compared with Ad-GFP + BSA, the abundances of PTEN and of fatty acid oxidation-and VLDL assembly-related proteins were lower in the Ad-GFP + 1.2 mM FFA group. Importantly, PTEN knockdown heightened the increase in triglyceride accumulation of hepatocytes and the decrease in VLDL content in culture medium induced by FFA. Overall, these in vitro data indicate that FFA inhibits PTEN … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 44 publications
(50 reference statements)
1
6
0
Order By: Relevance
“…Our data revealed that high NEFA inhibited mRNA expressions of MTP, ApoB100, and ApoE, and thus suppressed the secretion of VLDL into the supernatants. The result was in line with previous studies [ 10 , 20 , 26 ]. Those data together support a central role of high NEFA in the TAG accumulation in hepatocytes and further in the initiation and progress of fatty liver in cows, highlighting a feasibility of treating or preventing fatty liver by blocking the detrimental effects of excessive NEFA.…”
Section: Discussionsupporting
confidence: 93%
“…Our data revealed that high NEFA inhibited mRNA expressions of MTP, ApoB100, and ApoE, and thus suppressed the secretion of VLDL into the supernatants. The result was in line with previous studies [ 10 , 20 , 26 ]. Those data together support a central role of high NEFA in the TAG accumulation in hepatocytes and further in the initiation and progress of fatty liver in cows, highlighting a feasibility of treating or preventing fatty liver by blocking the detrimental effects of excessive NEFA.…”
Section: Discussionsupporting
confidence: 93%
“…Fatty acid oxidation is a key biological process within the liver that helps regulate not only energy availability to liver cells, but also water-soluble fuels in the form of ketone bodies that peripheral tissues can use (Zhao et al, 2020). Activity of CPT1A regulates the entry of fatty acids into mitochondria before entry into β-oxidation (Li et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…PTEN functions as the most critical inhibitor of the PI3K pathway. Surprisingly, both PTEN inhibition and expression inhibit β‐oxidation, most likely via two different mechanisms; one mechanism is dependent on the PI3K/AKT pathway, and the other is independent 47,48 . The mechanism of the latter remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, both PTEN inhibition and expression inhibit β-oxidation, most likely via two different mechanisms; one mechanism is dependent on the PI3K/AKT pathway, and the other is independent. 47,48 The mechanism of the latter remains unknown. On the one hand, functions associating with PTEN nuclear localization might explain the underlying mechanism.…”
Section: Discussionmentioning
confidence: 99%